A Self-Adaptive and Wide-Range Conductivity Measurement Method Based on Planar Interdigital Electrode Array - Wang, Xiaolei; Wang, Yuhao; Leung, Henry; Mukhopadhyay, Subhas Chandra; Chen, Shaoping; Cui, Yongqiang (IEEE access, 2019)
Conductivity is a crucial parameter in water quality detection, which can roughly represent overall concentration of various inorganic ions. However, traditional conductivity sensors can only afford high performance measurement in a relatively low range while the concentration may vary much more in realworld water environment. This paper proposes a high-precision and wide-range measurement method based on a novel planar interdigital electrode sensor array and a self-adaptive algorithm. The array is composed of 3 pairs of planar electrodes with various cell constants aiming at different subdivided conductivity sections. The follow-up circuit and the self-adaptive algorithm keep the optimal electrode pair dominates the output of the array. Numerical simulations were utilized to optimize sensor parameters before fabrication. PCB manufacturing technique was used which guaranteed a relatively low manufacturing cost and stable performance. Experiments were conducted to verify the sensing performance and results showed that the array can maintain precise measurement from 0.5μs/cm to 500ms/cm.